Growth-related changes in anthropometry and physical fitness in girls aged 10-13 years - Katsikadelis Michail; Đokić Zoran (University Educons, Faculty of Sports and Tourism, Novi Sad, 2020)
This study is aimed at evaluating 10-13-year-old girls' motor skills and anthropometric characteristics as well as their interrelationships during their growth. Three hundred seventy-eight girls from elementary schools underwent a standard anthropometry (body height, weight and body mass index) and motor fitness tests (sprint run for 20 meters, Bent knee push-up, sit-up test for 30 seconds, standing long jump and sit and reach). Data was stratified by age. Age-specific percentile values (i.e., P5 to P95) were generated. Significant age-related main effects for body height, body weight, and body mass indexes were observed, including running speed, abdominal strength, and muscle endurance, as well as the explosive leg power. Physical fitness was considerably affected by anthropometric parameters. Body height seemed to be positively correlated with the explosive leg power and abdominal strength and muscles endurance, and negatively with speed, strength and endurance of the upper body muscle groups. Test results for assessing strength were insufficient. Likewise, body weight appeared positively correlated with explosive leg power and negatively with speed, strength and endurance of the upper body muscle groups and flexibility. As for the body mass index, it was proven to be negatively correlated with strength and the endurance of the upper body muscle groups and flexibility.